A lower motor neuron disease in takahē (Porphyrio hochstetteri) is an endoplasmic reticulum storage disease. - Jolly RD; Perrott MR; Alley MR; Hunter SA; Pas A; Beard H; Hemsley KM; Greaves G (Taylor and Francis Group, 2023)
AIMS: To investigate the pathogenesis of a disease in takahē (Porphyrio hochstetteri) with intracytoplasmic inclusion bodies in lower motor neurons. METHODS: Four birds aged between 5 and 12 years, from three different wildlife sanctuaries in New Zealand were examined. Of these, only one had signs of spinal dysfunction in the form of paresis. Stained paraffin sections of tissues were examined by light microscopy and immunostained sections of the ventral horn of the spinal cord by confocal microscopy. Epoxy resin sections of the spinal cord from the bird with spinal dysfunction were examined by electron microscopy. RESULTS: Two types of inclusion bodies were noted, but only in motor neurons of the ventral spinal cord and brain stem. These were large globoid eosinophilic bodies up to 5 µm in diameter, and yellow/brown granular inclusions mostly at the pole of the cell. The globoid bodies stained with Luxol fast blue but not with periodic acid Schiff (PAS), or Sudan black. The granular inclusions stained with Luxol fast blue, PAS and Sudan black. Both bodies were slightly autofluorescent. On electron microscopy the globoid bodies had an even electron-dense texture and were bound by a membrane. Beneath the membrane were large numbers of small intraluminal vesicles. The smaller granular bodies were more heterogeneous, irregularly rounded and membrane-bound accumulations of granular electron-dense material, often with electron-lucent vacuoles. Others were more vesicular but contained varying amounts of electron-dense material. The large globoid bodies did not immunostain for lysosomal markers lysosomal associated protein 1 (LAMP1) or cathepsin D, so were not lysosomal. The small granular bodies stained for cathepsin D by a chromogenic method.A kindred matrix analysis showed two cases to be as closely related as first cousins, and another case was almost as closely related to one of them, but the fourth bird was unrelated to any other. CONCLUSIONS: It was concluded that this was an endoplasmic reticulum storage disease due to a specific protein misfolding within endoplasmic reticulum. It was rationalised that the two types of inclusions reflected the same aetiology, but that misfolded protein in the smaller granular bodies had entered the lysosomal system via endoplasmic reticulum autophagy. Although the cause was unclear, it most likely had a genetic aetiology or predisposition and, as such, has clinical relevance.
Keywords: Takahē; endoplasmic reticulum storage disease; inclusion bodies; lower motor neuron; proteinopathy; Animals; Cathepsin D; Endoplasmic Reticulum; Motor Neuron Disease; Microscopy, Electron; Birds